SAWAHLUNTO REVISITED: SOME NOTIONS ON URBAN REGENERATION OF FORMER OLD MINING TOWN - Maya Rosa (Fakultas Seni Rupa dan Desain ITB, 2022)
Adaptive reuse is one of the dynamic intervention activities following the current conservation paradigm, from the maintenance of cultural heritage objects to a dynamic utilization action. Nominated in 2015 and confirmed in 2019 as a UNESCO World Heritage Site, Sawahlunto, locally known as Kota Arang, is facing several issues on urban regeneration for the sustainability of the city. After the peak of coalmining period, the historical sites finally closed in 2001. Sawahlunto was left with massive and significant historic old mining urban heritage assets, tangible, and intangible. This paper aims to analyze the adaptive reuse activities carried out in the historic coal mine city of Sawahlunto concerning the regeneration of the city’s cultural heritage. The research approach used was descriptive qualitative using data collection methods from the field and case studies taken from the academic literature. This study shows that the success of adaptive reuse activities as an effort of urban regeneration is based on the involvement and satisfaction of the community as the living heritage in the historic city. Community involvement in creating spaces and turning them into cultural spaces to conserve the city’s cultural heritage can foster a sense of belonging and a sense of identity, which will be an essential factor in its sustainability. It can furthermore generate and stimulate economic activities as well.